Necesidad de Regular en el Código del Trabajo, la garantía del acceso al empleo de las mujeres garantizada en la Constitución de la Republica del Ecuador - Abad Alberca, Concepción Victoria (2015)
The Article 331 of the Constitution of the Republic of Ecuador, guarantees women access to employment, this is a fundamental right of women, that the Constitution of the Republic of Ecuador, considered the playing field in the access to employment, ie equal before the law in relation to work, and this is a category of constitutional principle, which must be respected and enforce both public and private sectors. The equal work for women and especially pregnant women and single mothers, has been guaranteed in our Constitution, as these people have always been neglected and discriminated against. Being new in this day and have started to enforce their rights, unfortunately not everyone respects, so is the need to establish appropriate sanctions in both public and private institutions, when they fail to meet the inclusion female labor both pregnant and single mothers. Pregnant women are protected as rights of individuals and focus groups, in which the state guarantees non-discrimination policies for their pregnancy in the educational, social and employment, it seeks to provide equal opportunities in access to work in any field, provided they meet the minimum standards of protection and care of women. In Article 41 of the Labour Code was established by the Employment Protection Act of Women, hire a minimum percentage of workers, but that provision was repealed by Legislative Decree No. 8, published in Official Gazette Supplement 330 of May 6 2008, which is ineffectual return to work of workers. The aim in this project is to regulate the access to employment of women in the labor code, ensuring the constitutional right of equality to work under fair and humane and aims to eliminate all forms of discrimination. Access to women's work is not guaranteed in the Labour Code, which is the standard that governs the relationship between employers and workers, do not set the appropriate punishment to be given in both public and private institutions, if not respected or not guarantee inclusion in the work of women and especially pregnant women and single mothers, so it is necessary to its proper regulation within this body of law, and in this way seek to enforce their rights in the equalization of opportunities for women on equal terms with men. Should also be noted that if there are no appropriate sanctions are not going to respect the right of women to work in conditions of equal opportunity, to promote their skills and potentials, through policies that allow incorporation into public entities and private. The Arts. 325 and 326 of the Constitution of the Republic of Ecuador, 2008, are explicit in referring to the rights enjoyed by male and female workers, which unfortunately are not respected by the business class, as it is known to all who are constantly disrespected and unobserved. The Labour Law is characterized by the ability to grant or grants to State agencies as through special procedures of public administration, prevent the violation of the labor law , control the fulfillment of the obligations of workers and employers , and attempt to resolve some of the conflicts that arise in the workplace